Bathya brevicarpus gen. et sp. nov. (Amphipoda: Senticaudata: Calliopiidae), from hydrothermal vents, Okinawa Trough, North-west Pacific - Wang, Yan-Rong; Zhu, Chao-Dong; Sha, Zhong-Li; Ren, Xian-Qiu (European Journal of Taxonomy, 2020)
One individual referable to Calliopiidae G.O. Sars, 1893 was collected from a chemically reduced habitat, the hydrothermal vent systems in Okinawa Trough, and was identified as a new genus and species belonging to this family after a morphological examination. A formal description of this new species and a discussion of the relationship of the new genus within Calliopiidae are presented.